2016
DOI: 10.1177/2047487316658571
|View full text |Cite|
|
Sign up to set email alerts
|

Parity, breastfeeding and risk of coronary heart disease: A pan-European case–cohort study

Abstract: 67Objective: There is uncertainty about the direction and magnitude of the associations between parity, breastfeeding and the 68 risk of coronary heart disease (CHD). We examined the separate and combined associations of parity and breastfeeding 69 practices with the incidence of CHD later in life among women in a large pan-European cohort study. 70Methods: Data were used from EPIC-CVD, a case-cohort study nested within the EPIC prospective study of 520,000 71 participants from 10 countries. Information on rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 38 publications
(75 reference statements)
2
51
2
3
Order By: Relevance
“…Among women younger than 65 years, there was some evidence of a U‐shaped relationship between lifetime duration of breastfeeding and the risk of CVD death, with women who reported lifetime breastfeeding duration of 7 to 12 months having half the risk than those who had breastfed for ≥2 years. In contrast, the EPIC (European Prospective Investigation into Cancer and Nutrition)‐CVD case‐cohort study, among 15 000 women with 5000 incident cases of CHD, found an inverse association between breastfeeding and the risk of CHD at all ages 12. The risk of CHD was the lowest among those who had breastfed for the longest durations, suggesting that prolonged durations of breastfeeding confer additional coronary benefits.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Among women younger than 65 years, there was some evidence of a U‐shaped relationship between lifetime duration of breastfeeding and the risk of CVD death, with women who reported lifetime breastfeeding duration of 7 to 12 months having half the risk than those who had breastfed for ≥2 years. In contrast, the EPIC (European Prospective Investigation into Cancer and Nutrition)‐CVD case‐cohort study, among 15 000 women with 5000 incident cases of CHD, found an inverse association between breastfeeding and the risk of CHD at all ages 12. The risk of CHD was the lowest among those who had breastfed for the longest durations, suggesting that prolonged durations of breastfeeding confer additional coronary benefits.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies of mostly Western populations have reported conflicting results on the relationship between breastfeeding and the risk of CVD. [10][11][12][13][14] In the US Nurses' Health Study of 90 000 parous women with 2500 cases of CHD, there was a threshold in the association between breastfeeding and CHD; only women with a lifetime duration of breastfeeding of ≥2 years had a significantly lower risk of CHD than those who never breastfed. 13 The HUNT trial (Nord-Trøndelag Health Study) 14 of 20 000 Norwegian women reported that the inverse association between a history of breastfeeding and CVD mortality was modified by age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current issue of this journal, the paper by Peters and associates 22 presents a case-cohort study that tracked 14,917 women from ten European countries who had no known history of CHD or stroke at baseline and who provided reproductive histories. Incidence rates of fatal and nonfatal CHD over 11 years of follow-up with regards to parity, number of children, breastfeeding and duration of breastfeeding were analysed.…”
mentioning
confidence: 99%